Utility of Point-of-care Ultrasound in Children With Pulmonary Tuberculosis. Issue 7 (July 2018) - Bélard, Sabine; Heuvelings, Charlotte C.; Banderker, Ebrahim; Bateman, Lindy; Heller, Tom; Andronikou, Savvas; Workman, Lesley; Grobusch, Martin P.; Zar, Heather J.
Abstract : Background: Point-of-care ultrasound (POCUS) detects extrapulmonary tuberculosis (EPTB) in HIV infected adults but has not been evaluated in children despite their higher risk of EPTB. This study's aims were to investigate feasibility of POCUS for EPTB in children, frequency of POCUS findings suggestive of EPTB and time to sonographic resolution of findings with treatment. Methods: This prospective South African cohort study enrolled children with suspected pulmonary tuberculosis (PTB). POCUS for pleural, pericardial or ascitic effusion, abdominal lymphadenopathy or splenic or hepatic microabscesses was performed and repeated at 1, 3 and 6 months of tuberculosis (TB) treatment. Prevalence of POCUS findings and their association with HIV infection was investigated in children with confirmed PTB (microbiologically proven), unconfirmed PTB (clinically diagnosed) or unlikely TB (respiratory disease that improved during follow-up without TB treatment). Results: Of 232 children [median age 37 months (interquartile range, 18–74)], 39 (17%) were HIV infected. Children with confirmed or unconfirmed PTB had a higher prevalence of POCUS findings than children with unlikely TB [18 of 58 (31%) and 36 of 119 (30%) vs. 8 of 55 (15%); P = 0.04 and P = 0.03, respectively]. Pleural effusion [n = 30 (13%)] or abdominal lymphadenopathy [n = 28 (12%)] were the most common findings; splenic microabscesses [n = 12 (5%)] were strongly associated with confirmed PTB. Children coinfected with HIV and TB were more likely than HIV-uninfected children with TB to have abdominal lymphadenopathy (37% vs. 10%; P < 0.001) or splenic microabscesses (23% vs. 3%; P < 0.001]. Most ultrasound findings were resolved by 3 months with appropriate TB treatment. Conclusions: POCUS for EPTB in children with PTB is feasible. The high prevalence of findings suggests that POCUS can contribute to timely diagnosis of childhood TB and to monitoring treatment response. Abstract : Supplemental Digital Content is available in the text.